Severity Patterns of Temporomandibular Disorders in Young Adults with Suspected Clinical Features - Wajiha Malik, Sadaf Malik, Sheema Shakir, Asifullah Khan, Amra Qadeer, Waqar Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Temporomandibular disorders (TMD) being progressive disorder having relatively higher prevalence in young adults necessitates early recognition in order to prevent development of established TMD. Method: Using a structured proforma and the method of interview, data were collected from 162 subjects for the frequency of severity pattern of Temporomandibular joint disorders in young adults with suspected clinical features .TMD were classified as mild ,moderate, severe and individuals having no TMD. According to Fonseca’s questionnaire the severity was determined from collective score earned from the response of the patient. TMD was clinically classified as none if the score ranged between 0-15 points, mild if 20-40 points, moderate if 45-65 points and severe if 70-100 points. Score was obtained from response of the patient. Results: Study revealed that out of 162 patients with symptoms 16.0% were categorized as having no TMD, 40.15% as having mild TMD, 35.2% with moderate TMD and 8.6% representing severe TMD. Conclusion: The most significant category of the TMD severity pattern in the young adults of this study was the mild level of temporomandibular disorder. Subjects with moderate level of TMD according to Fonseca’s questionnaire should be referred to the specialist clinic for the treatment of established TMD.